Zbirka plemiških portretov Jožefa Breznika s Koga pri Ormožu in njen osrednji del Galerija Dienerspergiana - Golec, Boris (Acta historiae artis Slovenica, 2025)
In 1934, the National Museum in Ljubljana purchased a collection of thirty-nine noble portraits from Jožef Breznik, a landowner at Kog near Ormož. The paintings were part of the estate of Antonia Kofler, née Baroness Dienersperg, the former owner of Breznik’s property. Half of the portraits came from the Dienersperg family from Dobrna near Celje and the other half from the Barons Adelstein from the Dobrnica Mansion near Dobrna, where Antonia’s grandmother came from. In about 1832, Antonia’s grandfather, Baron Franz Xaver Dienersperg, the owner of the Dobrna and Dobrnica mansions, added uniform inscriptions to the portraits at Dobrna. These were the sixteen portraits of Styrian and Carniolan Dienerspergs and two portraits of their relatives from the Hohenwart and Strassberg families, which were given the collective name Galeria Dienerspergiana. A single painter is signed, the hitherto little-known Andreas Peric. One of the earlier oil paintings was believed to be the portrait of Regina Constantia von Dienersperg, the long--forgotten youngest daughter of the Carniolan polymath Johann Weikhard von Valvasor.
Keywords: Adelstein (rodbina); Adelstein family; Andrej Peric; Dienersperg (rodbina); Dienersperg family; Dobrna Manor; Dobrna, grad; Hohenwart (rodbina); Hohenwart family; Jožef Breznik; oil paintings; oljne slike; portrait paintings; portretno slikarstvo; Strassberf family; Strassberg (rodbina); Valvasor (rodbina); Valvasor family